Spector and Kitsuse’s ‘Radical’ Theory of Social Problems, Forty Years On - Schneider, Joseph (SocietàMutamentoPolitica, 2018)
Malcolm Spector and John I. Kitsuse called their constructionist social problems theory “radical” relative to what had been offered before in the sociology of social problems. In this brief essay I argue that the radical ideas of their Constructing Social Problems remain, in many ways and some forty years later, still quite radical next to most of what is written in sociology under the banner “social problems.” Reconsidering those radical elements is the aim here, making clear just what that claim summarizes as both the excitement the theory still offers us and, at the same time, the grounds for it being resisted by most professional sociologists.